Analysis and Performance Validation of CRONE Controllers for Speed Control of a DC Motor - Velmurugan, V.; Venkatesan, M.; Praboo, N. N (International Journal of Robotics and Control Systems, 2024)
In recent decades controllers play a major role for an efficient control and reliable operation of an industrial process. Hence in this paper, a special kind of Commande Robuste d’Ordre Non Entier (CRONE) controller is designed for controlling the speed of DC Motor (DCM). The proper design procedure of two generations CRONE control strategies named as First-Generation CRONE (FGC) and Second-Generation CRONE (SGC) controllers are implemented through the transfer function of armature-controlled DCM. Simulations are performed on MATLAB software in order to investigate the servo responses of two designed CRONE controllers, besides the results are presented in terms of settling time(ts), rise time(tr), Integral Square Error (ISE) and Integral Absolute Error (IAE). In addition, the relay PI controller is designed and the simulation results are presented for comparison purpose. It is evident from the comparing results that the SGC controller is superior for effective process control.